Applied research of modulation-coding schemes selection algorithms effectiveness in 802.11 equipment - Uryvsky, Leonid; Moshynska, Alina; Osypchuk, Serhii (2017 4th International Scientific-Practical Conference Problems of Infocommunications. Science and Technology (PIC S&T), 2017)
In modern 802.11 equipment the algorithms are implemented that control MCS (Modulation-Coding Schemes) selection depending on the statistical data of successfully transmitted and lost data packets, without taking into account the energy conditions in the communication channel. In this paper, an applied experiment is performed in point-to-point (PtP) link with the study of the algorithm for MCS switching using the same communication equipment, with manual changing energy conditions in the communication channel. As a result, the correspondence was obtained for the MCS of 802.11n standard and communication channel energy characteristics, what is opposite to the statistical data of transmitted and received packets.